Indian economy sinse independence - Venkatasubbiah, H. (Bombay, 1958)
Simply stated, to raise living standards as soon as possible and at the same time to preserve the spirit as well. the form of freedom and democratic government is the present problem of India. The Indian effort at economic development is sometimes compared with what our great neighbour China has been making in the same direction but under a political system that is funda mentally different from the liberal democracy well understood in the Commonwealth of Nations, though not equally well practised by all its members. It seems to me that the comparison is both unnecessary and undesirable. In his Reith Lectures, Mr. George Kennan deprecated the American complex that the United States was now in competition with the Soviet Union and the apprehen sion that Russia may win the race'. America is in competition with itself, he pointed out. "The real competition is rather to see who moves most rapidly and successfully to the solution of his own peculiar problems and to the fulfilment of his own specific ideals." Something similar applies to the India-China comparison. India is in competition with itself-with its inertia, its men and women who are admirable individually but who, collectively, some how add up to something less than the sum of their individual personalities, its extremes of materialistic greed and spiritualistic (or pseudo-spiritualistic) apathy, the legacies of caste and language in the disposition of democratic power, and various forms of social and intellectual obscurantism. If the country takes longer to win the race against its problems than China does to win against its, it cannot and does not mean that planning under dictatorship is superior to planning under freedom, which is what India is attempting.
Keywords: Economics